Deconstruction of Devinity Theory in Islamic Theology: Philosophical Criticism of Theology as Theoretical Activity - Wahyudin, Wahyudin; Suhirman, Suhirman; Elhany, Hemlan (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
The doctrine of God in Islam was built as a supreme tradition, in which infiltrate into mankind souls. For centuries, Islam is deemed as an outsider and a threat for Western Christian followers. Consequently, any actions are taken to devastate Islam from the earth. Philosophically, this study aims to fortify Islamic theology againts political attacks particularly in separating Muslims from the concept of monotheism. This study employs a critical analysis method, a concept of sharp reasoning to obtain truth. The theory used to reduce metanarrative and elements of deconstruction is the Imre Lakatos research program, in which Islam means conformity or compatibility, harmony and logic. In the core of Islam, monotheism means Allah is One. It has “protective shields”which are the Holy Quran, hadith[s], and the theory of causality. The results of the study argue that the construction of divinity in Islam is solid and powerful and leads to a failure of criticism.